Association between RNF213 p.R4810K and Progression of Cerebral Artery Negative Remodeling in Moyamoya Disease - Haruto UCHINO; Masaki ITO; Taku SUGIYAMA; Kota KURISU; Noriyuki FUJIMA; Miki FUJIMURA (Neurologia Medico-Chirurgica, 2025)
Negative remodeling, characterized by a decrease in the outer diameter of the terminal (C1) segment of the internal carotid artery and the proximal (M1) segment of the middle cerebral artery, is a hallmark of moyamoya disease. However, the role of the disease-susceptibility gene RNF213 in negative remodeling in moyamoya disease remains unclear. This study investigated the effect of RNF213 p.R4810K polymorphism on the degree of negative remodeling in moyamoya disease. We analyzed 70 hemispheres of 38 adult patients with moyamoya disease who underwent RNF213 p.R4810K gene analysis. Vascular outer diameters of the distal C1 and proximal M1 segments were measured using constructive interference in steady-state images obtained from 3-tesla magnetic resonance imaging. Suzuki stages were determined via cerebral angiography, and comparisons were made between RNF213-mutant and wild-type hemispheres. Among the analyzed hemispheres, 39 (56%) were RNF213-mutant, and 31 were wild-type. Suzuki stages were distributed as follows: 0 in 8 hemispheres, 1-2 in 15, 3-4 in 40, and 5-6 in 7. At stage 3-4, the C1 outer diameter was significantly smaller in RNF213-mutant hemispheres compared to wild-type (median 2.1 vs 2.6 mm, p < 0.05). A significant reduction in vascular outer diameters in the advanced disease stage was observed only in the mutant group between stages 0 and 3-4 (C1: median 3.0 vs 2.1 mm, p < 0.05; M1: median 2.2 vs 1.5 mm, p < 0.001). These findings suggest the association between RNF213 p.R4810K polymorphism and the progression of negative remodeling at the carotid fork in advanced disease stages of moyamoya disease.